An MRI Study of the Metabolic and Structural Abnormalities in Obsessive-Compulsive Disorder - Salles Andrade, Juliana B. de; Ferreira, Fernanda Meireles; Suo, Chao; Yücel, Murat; Frydman, Ilana; Monteiro, Marina; Vigne, Paula; Fontenelle, Leonardo F.; Tovar-Moll, Fernanda (Frontiers in Human Neuroscience, 2019)
Obsessive-compulsive disorder (OCD) is a neuropsychiatric illness characterized by obsessions and/or compulsions. Its pathophysiology is still not well understood but it's known that the cortico-striatal-thalamic-cortical (CSTC) circuitry plays an important role. Here we used a multi-method MRI approach combining proton magnetic resonance spectroscopy (H1-MRS) and Diffusion Tensor Imaging (DTI) techniques to investigate both the metabolic and the microstructural white matter changes of the anterior cingulate cortex (ACC) in OCD patients as compared to healthy controls. Twenty-three OCD patients and 21 age, sex, and education matched healthy volunteers participated in the study. Our 1H-MRS findings shows increased levels of Glx in ACC in OCD. Further, significantly lower FA values were observed in OCD patients left cingulate bundle (CB) as compared to healthy controls. Finally, there was a negative correlation between FA in the left CB and level of obsessions, as well as the duration of the illness. Our findings reinforce the involvement of CSTC bundles in pathophysiology of OCD, pointing to a specific role of glutamate (glutamine) and white matter integrity.